DEVELOPMENT OF DOMINO CARD MEDIA IN SCIENCE LEARNING IN GRADE VI ELEMENTARY SCHOOL - Imam Khairurrijal; Bambang Hermansah; Puji Ayurachmawati (Universitas Majalengka, 2023)
This research is based on gathering information in the field that educators in learning have not presented many game activities. This study aims to produce domino card media in science learning in class VI SD with a valid, practical, and potential effect. This type of research is development research using the Borg & Gall model including 8 stages of research and information gathering, planning, initial product development, preliminary trials, revision of preliminary trial results, limited trials, extensive trials, final product revisions. This research was conducted in class VI of SD Negeri 235 Palembang. The results showed that the domino card media was in the